The big five of the monocot genomes. (April 2016) - Haberer, Georg; Mayer, Klaus FX; Spannagl, Manuel
Highlights: Monocots are a monophyletic clade including maize, wheat, rice, sorghum and barley. Complex monocot genomes were major targets for innovative sequencing projects. Sequenced genomes provide invaluable tools boosting crop research and breeding. Abstract : Monocots represent a monophyletic clade of the angiosperms that — based on fossil and molecular records — originated at around the Early Cretaceous from aquatic and wetland ancestors. Among their members are important crops including maize, wheat, rice, sorghum and barley, accounting for the major source for the daily calorie uptake by humans. Reflecting this importance, the partly large and complex genomes of these plants were major targets for ambitious and innovative sequencing projects, which will be discussed in this review article.